Proposal for the development of a web platform to improve the attention of specialized consultations on agricultural practices, 2023 - Castañeda Berrú, Mirian Medali (2023)
The objective of this research is to propose the development of a web platform for specialized consultations to improve the attention to agricultural practices presented by many farmers in our country. The research proposes to use the Java programming language under the object-oriented programming (OOP) paradigm following the Model-View-Controller (MVC) software architecture style. Finally, all the information entered by the web platform is stored in the MySql database manager. For the project's development, it was decided to use an agile methodology such as Scrum, which was divided in an optimal way in 4 Sprint. All the user stories that were obtained according to the needs presented were captured and covered during the development of the project, which allowed obtaining the best guidelines for the proposal of the web platform; finally, to guarantee the final proposal, surveys were conducted and the consistency was measured for its degree of reliability by applying Cronbach's Alpha, which provided a result of 0.924 reliability; thus, the proposal is validated in a satisfactory manner for the benefit of agriculture.